2016
DOI: 10.4238/gmr.15048819
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic diversity in a natural population of cambui tree (Myrciaria tenella O. Berg) using ISSR markers

Abstract: Cambui (Myrciaria tenella O. Berg) is a native species from Brazil, which belongs to the family Myrtaceae. Molecular characterization is one of the most used tools for the study of the biotechnological potential of species because the diversity level between individuals can be inferred. Analysis of genetic diversity is fundamental to the direction of the strategies necessary to form and maintain a germplasm. This study aimed to evaluate the genetic diversity in a natural population of cambui using inter-simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
(27 reference statements)
1
11
0
3
Order By: Relevance
“…This index can vary from 0 to 1, and the diversity is considered lower when values are closer to zero (Silva et al, 2015). In this study, the cambuizeiros with fruits of distinct coloring displayed an intermediate level of genetic diversity, similar to that observed by Santana et al (2016), which obtained (I) of 0.52.…”
Section: /8supporting
confidence: 86%
See 3 more Smart Citations
“…This index can vary from 0 to 1, and the diversity is considered lower when values are closer to zero (Silva et al, 2015). In this study, the cambuizeiros with fruits of distinct coloring displayed an intermediate level of genetic diversity, similar to that observed by Santana et al (2016), which obtained (I) of 0.52.…”
Section: /8supporting
confidence: 86%
“…In natural cambuizeiro population, Santana et al (2016) used 10 primers and obtained 70 polymorphic bands (98.3%). For the characterization of jabuticaba trees (Plinia sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Santana et al (2016) used ISSR markers to study the genetic diversity of Myrciaria tenella and found 71 polymorphic bands. Brandão et al (2011) evaluated the genetic structure of Myrcia splendens using 10 ISSR markers and found 70 polymorphic bands.…”
Section: Introductionmentioning
confidence: 99%